The prevalence of human T-lymphotropic virus infection among blood donors in southeast China, 2004-2013. - Jinzhen Xie; Shengxiang Ge; Yali Zhang; Yongcai Lin; Hongying Ni; Jun Zhang; Changrong Chen (Public Library of Science (PLoS), 2015)
BACKGROUND:The human T-lymphotropic virus type 1 (HTLV-1) which is associated with the diseases of adult T-cell leukemia/lymphoma, HTLV-1 associated myelopathy / tropical spastic paraparesis (HAM/TSP) and HTLV-associated uveitis, can cause transfusion-transmitted infections. Although HTLV screening of blood donors was already routinely performed in developed countries, little is know about the HTLV prevalence among blood donors in developing countries which do not perform HTLV screening, such as China. OBJECTIVES &AIMS:To systematically characterize the prevalence of HTLV infection among bloods in southeast China. METHODS:A 10-year survey for HTLV prevalence in blood donors was performed in Xiamen, southeast China, during 2004-2013. The HTLV-1/2 of blood donations were screened by enzyme-linked immunosorbent assay, following with confirmation by western blot assay and 9nucleic acid testing. The HTLV-1 prevalences in donors from different cities were calculated. Viral sequences derived from identified HTLV-positive cases were sequenced and analyzed. RESULTS:Among 253,855 blood donors, 43 were confirmed to be seropositive for HTLV-1 (16.9 per 100,000 95% CI: 12.3-22.8) and none HTLV-2 infection was found. The HTLV-1 prevalence varied significantly in donors from different cities. Donors from cities in Fujian province (24.3 per 100,000, 95%CI: 17.4-33.1) had a significantly higher (p=0.001) HTLV-1 seroprevalence than those who were born in non-Fujian cities (3.4 per 100,000, 95%CI: 0.7-9.8). Among nine cities in Fujian province, the highest prevalence was found in blood donors from Ningde (171.3 per 100,000, 95%CI: 91.3-292.8) which is a coastal city in the northeast of Fujian. Molecular characterization of viral sequences from 27 HTLV-1 carriers revealed 25 were Transcontinental subtype of genotype A and 2 were Japanese subtype of genotype A. Interestingly, 12 of 25 Transcontinental subtype sequences harbored a characteristic L55P mutation in viral gp46 protein, which was only presented in the Transcontinental subtype sequences from Japan and Taiwan but not in that from other countries. CONCLUSIONS:Although China is considered to be a non-endemic region for HTLV, the HTLV-1 prevalence in blood donors is significantly higher in Fujian province, southeast China. A higher prevalence of HTLV-1 in the Fujian may be attributed to endemic foci in the city of Ningde.